Hybrid Working and Work-Family Balance: New Challenges for HR Managers in Southeast Asia - Maula, Indi Millatul; Nabila, Maulina; Lestari, Ayu; Anwar, Saeful (Journal of Village Development Innovation, 2025)
Changing work models due to the COVID-19 pandemic have accelerated the adoption of hybrid work systems in Southeast Asia. While this model offers flexibility, major challenges arise in maintaining work-family life balance for employees, as well as managing productivity and well-being in diverse cultural contexts. This study aims to identify the challenges faced by HR managers in managing hybrid work systems in Southeast Asia, and evaluate their impact on employees' work-family life balance. This study used a quantitative approach with an explanatory design. Data was collected through a survey of 300 employees working in hybrid work models in six Southeast Asian countries and in-depth interviews with HR managers. The data analysis techniques used were descriptive and regression analysis. The findings show that HR managers in countries with better infrastructure, such as Singapore, are better able to manage the challenges of hybrid working. Countries such as the Philippines and Vietnam face more difficulties related to technological infrastructure and policies that are less supportive of work-life balance. The research suggests that HR managers adopt more flexible policies, improve training for HR managers, and provide technology that supports remote working. Policies tailored to local needs and attention to employee well-being are key to the success of hybrid working models in Southeast Asia.